AI-07 A new B cell effector pathway with defective negative regulation of TLR7 signaling in human SLE. (August 2018) - Jenks, Scott A; Cashman, Kevin S; Marigorta, Urko M; Sam Lim, S; Petri, Michelle; Anolik, Jennifer; Sanz, Ignacio
Abstract : Background: B cell homeostasis is perturbed in SLE patients. in particular, many patients have a large expansion of IgD- CD27- B cells (DN). The DN population is heterogeneous for CXCR5 expression, and CXCR5- DN2 are the majority population in SLE patients but not in HCD (figure 1A). To further understand how these expanded cells differ from other B cells subsets and how they may be dysregulated in SLE, we phenotypically and functionally characterized DN2 in SLE patients and healthy control donors (HCD). Methods: B cells subsets were quantified by flow cytometry in HCD and two separate cohorts of lupus patients. Purified DN2 and other B cell subsets were flow sorted and transcriptionally analyzed using RNA sequencing. Toll-like-receptor 7 (TLR7) signaling after stimulation with R848 was measured by staining with anti-phospho-tyrosine specific anti-ERK. Antibody secreting cell differentiation was induced using in vitro stimulation of sorted B cell subsets with a combination of TLR7 and cytokines. Results: DN2 were only a minor B cell subset in HCD (less than 5%) but were elevated in 20% of cohort 1 patients and 60% of cohort 2 (figure 1B). In the patients with the largest expansions almost all B cells (80%) had a DN2 phenotype. DN2 cells predominate in African-American patients with active disease and nephritis, anti-Smith and anti-RNA autoantibodies. Among B cells, they express the highest levels of a T-bet/Zeb2 transcriptional network characteristic of effector T cells and lack the negative TLR regulator, TRAF5. Consistent with this transcriptional profile DN2 are hyper-responsive to TLR7. Moreover, DN2 cells share with activated naïve cells phenotypic, functional features, and a very similar transcriptome. When stimulated in vitro DN2 readily differentiated into plasma cells and produced autoantibodies. Conclusions: DN2 and activated naïve represent a separate B cell lineage with a distinct origin and function as they differed from other B cells subsets both in uniquely expressing several genes and a lack expression of other genes. This study defines a distinct differentiation fate of human autoreactive naïve B cells into effector plasma cell precursors with innate hyper-responsiveness to stimuli relevant to SLE, establishes the components and prominence of extrafollicular B cell activation in this disease, and identifies new therapeutic targets.